Formatting work: Cloud platforms and the infrastructuring of capitalist asymmetries in software work - Randerath, Sebastian (Convergence (London, England), 2024)
Since the 2000s, so-called cloud computing infrastructures have had a profound impact on the capitalist relationship among labor, software, and organizations. This infrastructuring did not only affect the outsourcing of servers and databases but extends to the on-demand delivery of middleware and operating systems through so-called platforms-as-a-service (PaaS). As a result, the capitalist relationship between labor, organization, power, and software has shifted – both regarding the ways in which software development is organized and the ways in which work processes are organized through software. Such a shift is particularly evident in the development and application of so-called customer relationship management (CRM) software, which is used to plan and record sales and work processes. No longer limited to performance measurement and automated management within sales processes, the widely used Salesforce CRM software is leveraged to document and assess the work performance of employees meticulously, among other applications. To demonstrate how PaaS became central organizational media by reformatting labor and power asymmetries, the paper provides a critical analysis of the CRM software of Salesforce and the various actors and interfaces entangled with its PaaS. Thereby, the paper develops a critical media theoretical framework to analyze how the political economy of adapting PaaS is entangled with power dependencies between organizations and the labor of coding and implementing. Drawing on a platform historiographical analysis of Salesforce developer interfaces, the paper shows how organizational hierarchies and asymmetries manifest in the work of implementing specific sets of operational rules in software development (the work of formatting) and the platform capitalist standardization of work coordination in existing organizations (the formatting of work).